An Integrated Clinico-transcriptomic Approach Identifies a Central Role of the Heme Degradation Pathway for Septic Complications after Trauma. Issue 6 (December 2016) - Rittirsch, Daniel; Schoenborn, Veit; Lindig, Sandro; Wanner, Elisabeth; Sprengel, Kai; Günkel, Sebastian; Blaess, Markus; Schaarschmidt, Barbara; Sailer, Patricia; Märsmann, Sonja; Simmen, Hans-Peter; Cinelli, Paolo; et al.
Abstract : Objective: The present study was aimed to identify mechanisms linked to complicated courses and adverse events after severe trauma by a systems biology approach. Summary Background Data: In severe trauma, overwhelming systemic inflammation can result in additional damage and the development of complications, including sepsis. Methods: In a prospective, longitudinal single-center study, RNA samples from circulating leukocytes from patients with multiple injury (injury severity score ≥17 points; n = 81) were analyzed for dynamic changes in gene expression over a period of 21 days by whole-genome screening (discovery set; n = 10 patients; 90 samples) and quantitative RT-PCR (validation set; n = 71 patients, 517 samples). Multivariate correlational analysis of transcripts and clinical parameters was used to identify mechanisms related to sepsis. Results: Transcriptome profiling of the discovery set revealed the strongest changes between patients with either systemic inflammation or sepsis in gene expression of the heme degradation pathway. Using quantitative RT-PCR analyses (validation set), the key components haptoglobin (HP), cluster of differentiation (CD) 163, heme oxygenase-1 (HMOX1), and biliverdin reductase A (BLVRA) showed robust changes following trauma. Upregulation of HP was associated with the severity of systemic inflammation and the development of sepsis. Patients who received allogeneic blood transfusions had a higher incidence of nosocomial infections and sepsis, and the amount of blood transfusion as source of free heme correlated with the expression pattern of HP. Conclusions: These findings indicate that the heme degradation pathway is associated with increased susceptibility to septic complications after trauma, which is indicated by HP expression in particular. Abstract : Supplemental Digital Content is available in the text